Analysis of Tourism Development Components at the Museum Kota Juang Bireuen, Aceh Province - Zahara, Aida; Rahmi Novalita, Rahmi Novalita; Muharramsyah, Rambang (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This research aims to describe the components of tourism development at the Museum Kota Juang Bireuen. The research method uses a qualitative approach. Sources of research data through Inventory activities and tourism approaches. The informants in this research are key informants, while the informants in this research are the managers of the museum Kota Juang Bireuen. The technique for taking research informants uses the snowball technique (Snowball Sampling). Data collection techniques use observation, interviews and documentation. Data analysis uses data reduction, data display, and drawing conclusions. The research results show that the Museum Kota Juang has attractiveness as a cultural tourist attraction. This can be seen from various kinds of historical heritage objects. Accessibility conditions to the museum are very good and easy to find because it is equipped with signage or alleys to indicate the location. The museum kota Juang is close to the center of Bireuen City so that the area can be found with various supporting facilities such as restaurants, banks, ATMs, clinics, religious facilities, supermarkets, traditional markets. The museum Kota Juang, which is located close to the city of Bireuen, has various accommodations ranging from guesthouses, homestays and hotels as accommodation for visitors.